2000
DOI: 10.1073/pnas.170226797
|View full text |Cite
|
Sign up to set email alerts
|

Protection against hemorrhagic shock in mice genetically deficient in poly(ADP-ribose)polymerase

Abstract: Hemorrhagic shock (HS) and resuscitation leads to widespread production of oxidant species. Activation of the enzyme poly(ADPribose) polymerase (PARP) has been shown to contribute to cell necrosis and organ failure in various disease conditions associated with oxidative stress. We tested the hypothesis whether PARP activation plays a role in the multiple organ dysfunction complicating HS and resuscitation in a murine model of HS and resuscitation by using mice genetically deficient in PARP (PARP ؊͞؊ ) and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
117
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(123 citation statements)
references
References 36 publications
3
117
0
2
Order By: Relevance
“…In comparing mice genetically deficient in PARP with wild-type mice, the results indicate that PARP activation was associated with hepatic dysfunction and decreases survival. However, this damaging sequence of events was not seen in PARP-deficient mice with hemorrhagic shock (24). In addition, other studies of rats undergoing hemorrhagic shock and resuscitation have shown that the prevention of PARP activation decreases hepatic damage and dysfunction (28,45).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…In comparing mice genetically deficient in PARP with wild-type mice, the results indicate that PARP activation was associated with hepatic dysfunction and decreases survival. However, this damaging sequence of events was not seen in PARP-deficient mice with hemorrhagic shock (24). In addition, other studies of rats undergoing hemorrhagic shock and resuscitation have shown that the prevention of PARP activation decreases hepatic damage and dysfunction (28,45).…”
Section: Discussionmentioning
confidence: 90%
“…glutathione; redox state; caspases DESPITE ADVANCES IN THE EARLY CARE of trauma victims over the past two decades, multiple organ failure (MOF) continues to be a major factor in the morbidity and mortality that occurs after resuscitation from hemorrhagic shock (16). While there are numerous factors that influence the development of MOF, there is increasing evidence that hepatic dysfunction plays a central role (21,24,42,43). Experimental studies have shown that despite acute aggressive resuscitation, there is a consistent depression in microvascular blood flow that results in hypoperfusion and progressive hepatic dysfunction (32,42,43).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Considering that using fluid resuscitation alone in treating hemorrhagic shock would not be able to prevent MODS and mortality 11 , current research has diversified the search for solutions to prevent this complication. One aspect is combining drugs with fluid resuscitation solutions -drug therapy 4 .…”
Section: Introductionmentioning
confidence: 99%